Synchronized extracorporeal shockwave lithotripsy may still affect the heart: a case report of perioperative ST-segment elevation myocardial infarction - Li, Yi Hong; Hsu, Chao Yu; Liu, Chih Tsung; Lin, Yi Sheng; Ou, Yen Chuan; Tung, Min Che (Frontiers in Medicine, 2023)
Extracorporeal shockwave lithotripsy (ESWL) is widely used as a primary treatment for urolithiasis and is performed as an elective outpatient surgical procedure because of its ease of use. However, patients undergoing this treatment rarely develop cardiac complications. In this article, we present the case of a 45-year-old male patient who presented with ST-elevation myocardial infarction during ESWL. Moreover, atypical symptoms and electrocardiogram patterns were recognized by the nursing staff. Early primary evaluation and intervention resulted in favorable outcomes along with patent coronary artery flow following stent placement for stenosis, and no complications were noted.